A flexible perovskite homojunction with metallic ion doping for large-scale and high sensitivity X-ray detection. Issue 16 (11th April 2023) - Zhao, Jingda; Wang, Xin; Ding, Yijing; Wei, Ziyu; Xu, Yubing; Pan, Yuzhu; Li, Yuwei; Bae, Byung Seong; Furuta, Mamoru; Zhu, Zhuoya; Li, Qing; Zhou, Jianming; et al.
Abstract : A large-scale flexible X-ray detector based on a perovskite p–n homojunction is reported in this work. The addition of a Bi 3+ -doped MAPbI3 layer would effectively suppress the dark current and noise while maintaining high sensitivity. Abstract : High-sensitivity, large-scale, and low-cost flexible X-ray detectors are useful in many applications, such as medical and nondestructive imaging. MAPbX3 (MA = CH3 NH3 ; X = Cl, Br, and I) are promising materials because of their extraordinary optoelectronic properties and simple processing methods. Herein, we propose a novel perovskite-based p–n homojunction for large-scale and high-sensitivity flexible X-ray detectors, whose potential barrier can block electron injection transport, affording a low dark current. Incorporating Bi 3+ in MAPbI3 induces n-type doping without introducing lattice mismatch, minimizing photogenerated carrier losses. The doping concentration of the n-type layer was controlled to find a compromise between photo and dark currents of the X-ray detector, realizing a device with a high sensitivity of 1969.75 μC Gy −1 cm −2 and a low detection limit of 147 nGy s −1 . The fabrication process and storage were realized under ambient conditions, and no performance degradation was observed after our device was stored for one month under ambient conditions with 30–50% humidity. Finally, a 100 cm 2 flexible X-ray detector was fabricated to verify its ability for large-scale X-ray imaging. This study provides new insight into reducing noise in large-scale and flexible perovskite-based devices.